2022
DOI: 10.1590/fst.107621
|View full text |Cite
|
Sign up to set email alerts
|

Selected lactobacilli strains inhibit inflammation in LPS-induced RAW264.7 macrophages by suppressing the TLR4-mediated NF-κB and MAPKs activation

Abstract: Probiotics are known to provide the host with immune-modulatory effects, which is widely used for the treatment of inflammatory bowel disease (IBD), diarrhea, and ulcers.Lactobacillus acidophilus KLDS 1.0901, Lactobacillus helveticus KLDS 1.8701, and Lactobacillus plantarum KLDS 1.0318 were isolated from Chinese fermented dairy food with antibacterial activity, antioxidant activity, and immunomodulatory activity, respectively. This study evaluated the anti-inflammatory potential of the tested strains in LPS (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…To prevent or treat inflammatory diseases, inhibition of iNOS overexpression is crucial. The production of NO is closely associated with alterations in the expression levels of its synthesizing enzyme, iNOS [ 40 , 47 ]. Researchers have shown that various probiotic Bifidobacterium , Lactobacillus , and Weissella strains inhibit NO production in RAW 264.7 cells or murine bone marrow-derived macrophages (BMDMs) [ 23 , 40 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent or treat inflammatory diseases, inhibition of iNOS overexpression is crucial. The production of NO is closely associated with alterations in the expression levels of its synthesizing enzyme, iNOS [ 40 , 47 ]. Researchers have shown that various probiotic Bifidobacterium , Lactobacillus , and Weissella strains inhibit NO production in RAW 264.7 cells or murine bone marrow-derived macrophages (BMDMs) [ 23 , 40 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies by inhibiting the mechanism of bacterial-host cell interactions will help provide new ideas for drug targeting actions. In recent years, more and more studies have confirmed that edible probiotics and their metabolites are widely used for food preservation and regulation of human health and immunity (Pato et al, 2022;Shi et al, 2022). Therefore, in the food industry, it is more highlighted that the selection and breeding of high-yielding PLA strains, metabolic regulation, and the mechanism of their inhibition of spoilage and pathogenic bacteria still need more in-depth research, so that the application of PLA is more extensive.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that the Lactobacillaceae family includes many genera such as Lactobacillus , Paralactobacillus , and Pediococcus. Zheng et al ( 112 ) showed extensive diversity of the genus Lactobacillus , an integral part of the microbiome with anti-inflammatory action ( 113 ). Some studies associated decrease in Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%